MULTIAXIAL MANNED CENTRIFUGE INTENSITY VERIFICATION CALCULATION METHOD BASED ON MULTIBODY DYNAMICS - YUE CongZhen; NIU HongPan; WANG PengFei; FAN ZhiGeng; YIN JiaoMei (Jixie qiangdu)
The multi-axis manned centrifuge is an important device for training pilots' directional cognitive ability and overcoming illusions. Its intensity check is a necessary part of structural design. The traditional quasi-static static analysis method can only directly analyze the structural strength problem of no more than two-axis nested rotation, but the multi-axis manned centrifuge has three or more than three-axis nested rotation. The flexible multi-body dynamics method can be used to analyze and determine the strength of the multi-axis rotating structure of the motion path, but the calculation time is long and the resource consumption is large, so it is difficult to fully assess the intensity of the structure. In this paper, a multi-axis centrifuge intensity check method based on multi-body dynamics combined with random sampling and finite element calculation is proposed. The calculation results can be obtained in a relatively short period of time, it is highly efficient and feasible, which is conducive to improve the accuracy of structural intensity verification of multi-axis nested rotating equipment, and provides important support for its structural design.